BIOM-20. TUMOR-INTRINSIC AND PERIPHERAL FEATURES ASSOCIATE WITH SURVIVAL AFTER POLIO VIROTHERAPY IN RECURRENT GBM. (12th November 2021) - Brown, Michael; Zhang, Gao; Stevenson, Kevin; Lin, Xiang; Chen, Yeqing; Wei, Zhi; Beaubier, Nike; Yan, Hai; He, Yiping; Desjardins, Annick; Herndon, James; Varn, Frederick; et al.
Abstract: BACKGROUND: PVSRIPO is a live-attenuated recombinant rhino:poliovirus that mediates antitumor efficacy by engaging antitumor immunity. A subset ( 20%) of patients with recurrent GBM (rGBM) survive >24 months after therapy. We previously reported that low tumor mutation burden (TMB) is associated with longer survival after PVSRIPO and immune checkpoint blockade therapy in rGBM, and that low TMB associates with higher inflammatory gene expression signatures in rGBM tumors. METHODS: Clinical features were tested for association with survival after PVSRIPO therapy. Whole exome sequencing and RNA-sequencing of tumors were used to correlate mutational landscape, tumor mutation burden (TMB), and gene expression signatures of patient tumors with survival. An in vitro assay that measures inflammatory responses of patient PBMCs to PVSRIPO was performed. An independent cohort of paired primary and recurrent GBM tumors was used to assess longitudinal changes in TMB and gene expression signatures after standard of care treatment. RESULTS: A short time to recurrence and low TMB associated with longer survival after PVSRIPO therapy; these features were not prognostic for longer survival in immunotherapy naïve rGBM cohorts. Unexpectedly, higher pre-treatment polio neutralizing antibody titers were also associated with longer survival after PVSRIPO therapy in two independent clinical cohorts. PBMCs from patients surviving longer after PVSRIPO therapy mounted higher TNF, but lower IFN-a responses after in vitro challenge with PVSRIPO. In analysis of paired primary vs recurrent GBM tumors, we discovered that patients with low TMB upon recurrence were more likely to experience increased tumor inflammation and suppression of overall TMB. Low TMB in rGBM tumors was also associated with neoantigen depletion. Collectively, these observations imply that patients with low TMB and/or shorter duration of standard of care therapy may have intact immune surveillance, and that pre-treatment immunological status may dictate survival response to polio virotherapy.